Effect of extracts from nine plant species found in Africa on the mycelial growth of Aspergillus flavus Link - Cardwell, K.; Dongo, L. (1994)
Farmer survey conducted in 1991 and 1992 revealed that some farmer's combat storage moulds using locally available plants. Extracts and combination of extracts of nine different plant species that are used as traditional medicines and aromatic spices in Nigeria were tested for the effect in vitro on the growth of Aspergillus flavus. Aqueous extracts from the combination of dried fruits of xylopia aethiopica and dried seeds of piper guineense completely inhibited the growth of the fungus. Dried roots of the Zingiberaceae and fresh leaves of the Labiateae showed a range of fungistasis. Significant fungistatic effects were seen for all but two of the plant species tested, through some fungal inhabitation was short lived. Testing to identify efficacious plant species from various agroecological zones is continuing.